Psidium cattleyanum essential oil to control plant pathogens in bean seeds - Rocha, Cintia Hoffer da; Agostinetto, Lenita; Boff, Pedro; Werner, Simone Silmara; Soldi, Cristian; Boff, Mari Ines Carissimi (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The aim of this study was to evaluate the potential of Psidium cattleyanum essential oil for phytopathogen control in bean seeds. In order to obtain the oils P. cattleyanum was collected in four phenological phases. For each phase, pure oil, homeopathized oil 7CH (Hahnemannian centesimal dilution order) and 12CH were used and distilled water was the control. Eight replications were used, each with 25 seeds in petri dish. After seven days, germination and pathogen incidence were determined. Pure oil in the old leaves and new leaves phase and 7CH oil in the new leaves and flowering phase showed seed germination according to the certification legislation, above 70%. Fusarium oxysporum, Penicillium sp. and Aspergillus flavus were incident in all treatments. Lower incidence of A. flavus occurred with the use of pure oil and 7CH oil of new leaves and flowering and 12CH of flowering. Collection season for the extraction of P. cattleyanum oils influences its antifungal action.